PELAKSANAAN PROGRAM PUSAT PELAYANAN TERPADU PEMBERDAYAAN PEREMPUAN DAN ANAK (P2TP2A) DALAM MENANGGULANGI KEKERASAN DALAM RUMAH TANGGA DI PEKANBARU TAHUN 2012 - Sari, Bonita; Asrida, Wan (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2015)
Integrated Service Center Program Implementation Empower Women And Children (P2TP2A) Eradicate In Domestic Violence In Pekanbaru In 2012. To create a happy family welfare requires several things including aspects concerning health, economy, education and harmonious relationship. Marriage also requires physical maturity also mentally. If these things are not fulfilled, it is not uncommon that the sacred marriage will end in divorce. P2TP2A as one ministry programs to empower women and child protection in the form of agencies that provide services to women and children in order to fulfill the information and needs in education, health, economics, politics, law, protection and prevention of violence and trafficking of women and children. P2TP2A strategies that establish partnership relations in a way to include the role of the sector or related agencies, community organizations and the community in the management and execution of daily tasks. Because in principle P2TP2A formed of, by and for the community.A large number of physical violence, sexual, economic and psychological against women and children in the household in the city of Pekanbaru which has not been revealed due to still lack the willingness for people to report acts of violence they experienced because they bertanggapan that internal or personal affairs should not be interfered other party. In addition, many people also do not know the existence P2TP2A Pekanbaru for maximal implementation of outreach programs by P2TP2A itself.Keywords : Implementation, Professionalism , Resource.